2018
DOI: 10.1182/blood-2018-99-110164
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Change in CAR T Cell Manufacturing Can Impact in Expansion and Side Effect of the CAR T Cell Therapy

Abstract: Introduction: Chimeric antigen receptor (CAR)-modified T cells targeting CD19 can induce potent and sustained responses in children with relapsed/refractory acute lymphoblastic leukemia (rrALL). We previously reported a robust intent-to-treat product-manufacturing success rate of 100% in minimally selected, heavily pretreated patients with ALL in our Pediatric and young adult Leukemia Adoptive Therapy (PLAT)-02 phase 1 study (NCT02028455). Following completion of the Phase 1 study, a minimal change in CAR T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Cerebral edema has not been described with other CAR T cell products or other cancer immunotherapies. Cerebral edema has occurred in children and adults, in patients with ALL, NHL, and CLL, and in CD28 and 4-1BB costimulated CAR T cell products (7,28,(51)(52)(53)(54). Many of the hypotheses on ICANS pathophysiology are based on findings in patients with severe or fatal neurotoxicity, such as microvascular disruption, endothelial activation, and brain edema.…”
Section: Figure 1 | Correlation Of Incidence Of Neurotoxicity and Crsmentioning
confidence: 99%
“…Cerebral edema has not been described with other CAR T cell products or other cancer immunotherapies. Cerebral edema has occurred in children and adults, in patients with ALL, NHL, and CLL, and in CD28 and 4-1BB costimulated CAR T cell products (7,28,(51)(52)(53)(54). Many of the hypotheses on ICANS pathophysiology are based on findings in patients with severe or fatal neurotoxicity, such as microvascular disruption, endothelial activation, and brain edema.…”
Section: Figure 1 | Correlation Of Incidence Of Neurotoxicity and Crsmentioning
confidence: 99%
“…FasT CAR platform are able to concurrently activate and transduce resting T cells into a single “concurrent activation-transduction” step using XLenti vectors derived from lentivirus. An abstract from the ASH annual meeting shows that during CAR-T cell manufacturing each stage has different functional and metabolic requirements and small changes can have large effects on the efficacy and side effects of CAR-T cell therapy [ 7 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Out of 29 studies assessed, 26 studies (89.7%) were classified as having low risk of bias [ 17 , 21 , 24 , 26 , 30–41 , 43–45 ], while three studies (10.3%) possessed intermediate risk of bias [ 19 , 21–25 , 29 , 42 ]. No high-risk bias studies were found among the included studies.…”
Section: Resultsmentioning
confidence: 99%